Efek Pemberian Blondo dalam Ransum terhadap Total Koloni Lactobacillus sp, Salmonella sp dan Escherichia coli pada Ileum Broiler - E. Martinelly; Husmaini Husmaini; E. Purwati R.N.; R. Zein; R.M. Siagian (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
An experiment was conducted to study the effect of feeding by-product from virgin coconut oil processing (blondo) in ration on total colony of Lactobacillus sp, Salmonella sp and Escherichia coli in ileum of broiler. Broilers reared for 6 weeks in Unit Pelaksana Teknis (UPT), at Faculty of Animal Science, University of Andalas. One hundred of broilers strain Cobb on three days old were used. The design of experiment was a Completely Randomized Design (CRD), with 5 treatments (0; 7.5; 15; 22.5 and 30% blondo level in ration) and 4 replications for each treatment. Variables observed were total colony of Lactobacillus sp bacteria, Salmonella sp and Escherichia coli in ileum of broiler at 3 and 6 weeks of age. The result showed, total colony of Lactobacillus sp bacteria highly significant (P<0.01) increased and Salmonella sp highly significant (P<0.01) decreased by treatment at 3 and 6 weeks of age, but only decreased significantly (P<0.05) total colony of Escherichia coli bacteria at 3 weeks of age and highly significant decreased (P<0.01) at 6 weeks of age. The results showed that administration of 15% blondo in ration showed the most optimal results in creating a balance of microflora in ileum of broiler.An experiment was conducted to study the effect of feeding by-product from virgin coconut oil processing (blondo) in ration on total colony of Lactobacillus sp, Salmonella sp and Escherichia coli in ileum of broiler. Broilers reared for 6 weeks in Unit Pelaksana Teknis (UPT), at Faculty of Animal Science, University of Andalas. One hundred of broilers strain Cobb on three days oldwere used. The design of experiment was a Completely Randomized Design (CRD), with 5 treatments (0; 7.5; 15; 22.5 and 30% blondo level in ration) and 4 replications for each treatment. Variables observed were total colony of Lactobacillus sp bacteria, Salmonella sp and Escherichia coli in ileum of broiler at 3 and 6 weeks of age. The result showed, total colony of Lactobacillus sp bacteria highly significant (P<0.01) increased and Salmonella sp highly significant (P<0.01) decreased by treatment at 3 and 6 weeks of age, but only decreased significantly (P<0.05) total colony of Escherichia coli bacteria at 3 weeks of age and highly significant decreased (P<0.01) at 6 weeks of age. The results showedthat administration of15% blondoinrationshowedthemostoptimalresultsincreating abalance ofmicroflorain ileumof broiler.